(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
This paper analyzes the narrative techniques used by Amish Tripathi in his Ramachandra Series, which includes The Scion of Ikshvaku (2015), Sita: Warrior of Mithila (2017), Raavan: The Enemy of Aryavarta (2019) and War of Lanka (2022). A modern reimagining of the Ramayana, the series stands out for its distinctive storytelling methods such as non-linear structure, character-driven narratives, mythical realism, multiple viewpoints and rich use of symbolism and allegory. Tripathi presents each central character’s perspective on shared events, allowing readers to engage with the moral complexities and layered personalities within the epic. His use of contemporary language and accessible style bridges the gap between the ancient and the modern, making the narrative relevant to today’s readers. This study explores how these narrative techniques shape the retelling, enhance its appeal and contribute to a fresh, nuanced understanding of the Ramayana in contemporary literature.